STEAM Web Based Blended Learning Approach in Biodiesel to Improve Problem-Solving Ability, Conceptual Understanding, and Students’ Environmental Literacy - Syahmani; Yogo Dwi Prasetyo; Nika Sopranti; Milana Sari; Suyidno; Arif Sholahuddin (Universitas Pendidikan Ganesha, 2025)
The low problem-solving ability of chemistry students in solving contextual problems is related to their low conceptual understanding and environmental literacy. Based on these problems, this study aims to improve problem-solving abilities and conceptual understanding through the development of a biodiesel e-module with a valid, practical, and effective STEAM Web Based Blended Learning (STEAM WBBL) approach. This study uses the ADDIE model for research and development. This study was conducted on 40 Chemistry Education students of the Faculty of Teacher Training and Education. Data collection techniques used questionnaires and test instruments for problem-solving abilities, conceptual understanding, and environmental literacy. The effectiveness analysis technique used a written test in the form of problem-solving ability and conceptual understanding test instruments. Based on the validity test, the developed biodiesel e-module was declared valid, very practical, and effective in improving students' problem-solving abilities, conceptual understanding, and environmental literacy with N-gain values of 0.75, 0.73, and 0.68, respectively. The biodiesel e-module application with the STEAM WBBL approach is suitable for use as a teaching material.